Mapping food surveillance chains through different sectors - Amato, Laura; Benedetti, Guido; Di Giuseppe, Paola; Hénaux, Viviane; Lailler, Renaud; Nordeng, Zuzana; Scharffenberg, Tora Alexandra Ziesler; Skjerdal, Taran; Cito, Francesca (Frontiers in Public Health, 2023)
European countries are investing in strengthening disease surveillance within a One Health (OH) perspective. Mapping the components of existing disease surveillance systems is a fundamental step in understanding the relationships between its components, and subsequently facilitating their collaboration and integration under a OH approach. In this paper, we describe the methodological approach implemented during the MATRIX project, in the context of the One Health European Joint Programme, to investigate existing surveillance chains across different sectors. Two real-life scenarios are presented as case studies: the surveillance activities in place in France for Salmonella in the pork meat food chain, and in Norway for Listeria monocytogenes in the dairy food chain. The lessons learnt during the mapping process are also reported to share the advantages and drawbacks of the methodology.